A case of neuro traumatic paralytic keratitis - Campodónico, Esteban (1920)
Isidro Leon, 38 years old, born in Tacna, is a sturdy worker in the arrangement of cargo on board the steamer "Urubamba" which has suffered an accident at work, seeks relief for the consequences. The paucity of data referred our patient we could get the following: "On October 5, 1919 he was on board directing the placement of a shipment of starch, below deck and starboard of the ship, when in a given time, one lingada eight bags of starch, head resting on my right hand, I strongly compressed and made me violently tilt left on the side of the ship, tried to flee as heavy weight, escurriéndome protected by the same rail, of which also served me out to the middle of the boat, where I thought I fought quite remember when the accident happened, because I thought I felt at that moment that my eyes jumped, awful feeling I can not describe;.. after a while (about 10 minutes) I was losing my mind, I felt great lightheadedness, ringing in ears, my head was spinning and then fell dead. I tell my colleagues that left me very watery blood from the mouth, nose and right ear (where I continued out longer than through the mouth and nose); I was lying a long time and ship's doctor ordered me to put ice on my head and I moved to Hospital Mollendo port where the ship was at anchor. On the third day of the accident and in the hospital when I did the ear wash, I felt as if awakening from a deep sleep; and was a great suffering for me when I wanted to talk about, because he could not pronounce the words, I had no strength in my jaw and my mouth was twisted too far right, so that seemed very close to the ear. But they have done nothing to me, slowly I'm getting better, because before I could not gather the lips on this side, so it was hard to contain the liquid in the mouth, all escaped through the right side, when he ate much of piled food on this side, having to take them out with your finger. After the accident I have not been sweating on the right side of the face. For eight eight days I had a fever of 37 ° to 39 °. "